Meshed Architecture of Performance as a Model of Situated Cognition - Gallagher, Shaun; Varga, Somogy (Frontiers in Psychology, 2020)
In this paper, we engage in a reciprocal analysis of situated cognition and the notion of “meshed architecture” as found in performance studies (Christensen et al., 2016). We start with an account of various conceptions of situated cognition using the distinction between functional integration, which characterizes how an agent dynamically organizes to couple with its environment, and task dependency, which specifies various constraints and structures imposed by the environment (see Slors, 2019). We then exploit the concept of a meshed architecture as a model that provides a more focused analysis of situated cognition and performance. Through this analysis, we show how the model of meshed architecture can be enhanced through (1) the involvement of a more complex set of cognitive processes, (2) a form of intrinsic control, (3) the influence of affective factors, and (4) the role of factors external to the performer. The aim of this paper, then, is twofold: first to work out an enhanced conception of the model of meshed architecture by taking into consideration a number of factors that clarify its situated nature, and second, to use this model to provide a richer and more definitive understanding of the meaning of situated cognition. Thus, we argue that this reciprocal analysis gives us a very productive way to think about how various elements come together in skilled action and performance but also a detailed way to characterize situated cognition.